The reliability of the physical examination to guide fluid therapy in adults with severe falciparum malaria: an observational study - Hanson, Josh (BioMed Central, 2013)
BACKGROUND: Adults with severe malaria frequently require intravenous fluid therapy to restore their circulating volume. However, fluid must be delivered judiciously as both under- and over-hydration increase the risk of complications and, potentially, death. As most patients will be cared for in a resource-poor setting, management guidelines necessarily recommend that physical examination should guide fluid resuscitation. However, the reliability of this strategy is uncertain. METHODS: To determine the ability of physical examination to identify hypovolaemia, volume responsiveness, and pulmonary oedema, clinical signs and invasive measures of volume status were collected independently during an observational study of 28 adults with severe malaria. RESULTS: The physical examination defined volume status poorly. Jugular venous pressure (JVP) did not correlate with intravascular volume as determined by global end diastolic volume index (GEDVI; r(s) = 0.07, p = 0.19), neither did dry mucous membranes (p = 0.85), or dry axillae (p = 0.09). GEDVI was actually higher in patients with decreased tissue turgor (p < 0.001). Poor capillary return correlated with GEDVI, but was present infrequently (7% of observations) and, therefore, insensitive. Mean arterial pressure (MAP) correlated with GEDVI (r(s) = 0.16, p = 0.002), but even before resuscitation patients with a low GEDVI had a preserved MAP. Anuria on admission was unrelated to GEDVI and although liberal fluid resuscitation led to a median hourly urine output of 100 ml in 19 patients who were not anuric on admission, four (21%) developed clinical pulmonary oedema subsequently. MAP was unrelated to volume responsiveness (p = 0.71), while a low JVP, dry mucous membranes, dry axillae, increased tissue turgor, prolonged capillary refill, and tachycardia all had a positive predictive value for volume responsiveness of ≤50%. Extravascular lung water ≥11 ml/kg indicating pulmonary oedema was present on 99 of the 353 times that it was assessed during the study, but was identified on less than half these occasions by tachypnoea, chest auscultation, or an elevated JVP. A clear chest on auscultation and a respiratory rate <30 breaths/minute could exclude pulmonary oedema on 82% and 72% of occasions respectively. CONCLUSIONS: Findings on physical examination correlate poorly with true volume status in adults with severe malaria and must be used with caution to guide fluid therapy. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT00692627